Accounting in state-owned companies operated for the production and sale of alcohol in Russia in the fifteenth-seventeenth centuries. (August 2019) - Sokolov, Viatcheslav; Karelskaia, Svetlana; Zuga, Ekaterina
The purpose of this study is to research the accounting method used in state-owned companies operated for alcohol production and sale in Russia in the fifteenth–seventeenth centuries. Such an accounting method was distinguished by a variety of registers and entries according to a single-entry bookkeeping system. By the seventeenth century, this method had provided a framework for the emergence of a complex accounting system based on the principles of cameral accounting. This study presents the history of an accounting method used in state-owned companies in Russia before the advent of double-entry bookkeeping.